Precipitation behavior and strengthening mechanism of Ti micro-alloyed steel via CSP process. (2nd October 2019) - Liang, Wen; Zhang, Yongfu; Zhang, Lefu; Wu, Run
Abstract: Two types of micro-alloyed steel with different carbon content and coiling temperature were produced by compact strip production (CSP) process. The microstructure characteristics and precipitation behavior of the Ti particles during casting, soaking, rolling, coiling and cooling stages were discussed to reveal the strengthening mechanism. The samples were composed of ferrite bands and discontinuous pearlite/bainite at the grain boundaries. The average grain sizes of the sample with low carbon content and high coiling temperature was confirmed as 5.6 μ m by quantitative metallography method, while that with high carbon content and low coiling temperature was confirmed as 5.2 μ m. Moreover, the TiN precipitated before soaking stage was large in size because of the high undercooling temperature, which had nearly no strengthening effect. The strength was mainly attributed by cooling and coiling stages with the TiC precipitated at the inter-phase or within the ferrite. Taking Q345B steel with yield strength of 505 MPa produced by CSP as contrastive sample, the strength increments of fine-grain/solution/dislocation/precipitation strengthening for the low carbon sample were 65, 0, 22 and 113 MPa, while those for the high carbon sample were 74, 33, 28 and 57 MPa. Fine-grain and precipitation strengthening were the main strengthening mechanisms for the high strength CSP plates.